The COVID-19 in Omani children with chronic Hemato-oncology diseases: COVID-19 in Omani children with chronic Hemato-oncology diseases - Al Yazidi, Laila (Mediterranean Journal of Hematology and Infectious Diseases, 2020)
No abstract. This is a letter to the editor